Towards Secure, Flexible and Efficient Role Based Hospital’s Cloud Management System: Case Study - Harnal, Shilpi; Chauhan, R.K. (EAI Endorsed Transactions on Pervasive Health and Technology, 2020)
INTRODUCTION: Many organizations of health care have recognized that quality of service can be improved by maintaining e-records of patient’s reports, medical histories, surgeries recordings, etc. over the multimedia cloud servers. But, the data breach is always a matter of stake for an organization as well as for the patients.OBJECTIVES: This work has considered a qualitative scenario related to multimedia e-content management for a multiforte hospital’s cloud server.METHODS: An End-to-End Encryption with the cryptographic algorithm is applied along with an access control framework for secure transmission and storage of e-records.RESULTS: The results are presented in the form of bar graphs for the time taken to perform encryption/decryption of various media files and combo graphs for different scenarios of access control.CONCLUSION: This can provide prevention from many attacks/threats, ensures authentication and privacy along with limiting the server usage and cost.
Keywords: Cloud Computing; Role-Based Access Control; Access control; Security; DDOS; Multimedia cloud computing; Hospital; eHealth